Identifying the role of complement receptor 2 (CR2) on follicular dendritic cells (FDCs) in the persistence of foot and mouth disease virus (FMDV). Issue Volume 1(2019)Issue A (8th March 2019) - Gordon, Lucy; Mabbott, Neil; Charleston, Bryan; Perez, Eva
Abstract : More than 50 % of cattle (regardless of foot and mouth disease (FMD) vaccination) become persistently infected for long periods of time (years) after exposure to FMD virus (FMDV). The mechanisms associated with establishment of persistent infections are still poorly understood. I am testing the hypothesis that complement receptor 2 (CR2) on follicular dendritic cells (FDCs) located in the germinal centers of the lymphoid tissue, are involved in the trapping and long-term persistence of FMDV and that this persistence is essential for the maintenance of long-term antibody responses to FMDV. The aim of this study was to assess FMDV antigen retention and the generation of the specific immune response in vivo, in a mouse model. Groups of mice were treated with an anti-CR2 monoclonal antibody, named 4B2, which has been described previously to block CR2 long-term in vivo, blocking for 6 weeks after a single injection of 2 mg (Kulik et al., 2015). After treatment with 4B2, animals were infected with FMDV and lymphoid tissues and serum samples evaluated for the presence of antigen and the humoral immune response, respectively. The ability of 4B2 to block the binding of FMDV and PAP immune complexes (ICs) to FDCs in vitro as well as results about the role of FDC in trapping FMDV via CR2 in vivo is currently being investigated and will be discussed.